2014
DOI: 10.1002/glia.22781
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial fission and volume density by blocking glutamate excitotoxicity protect glaucomatous optic nerve head astrocytes

Abstract: Abnormal structure and function of astrocytes have been observed within the lamina cribrosa region of the optic nerve head (ONH) in glaucomatous neurodegeneration. Glutamate excitotoxicity-mediated mitochondrial alteration has been implicated in experimental glaucoma. However, the relationships among glutamate excitotoxicity, mitochondrial alteration and ONH astrocytes in the pathogenesis of glaucoma remain unknown. We found that functional N-methyl-D-aspartate (NMDA) receptors (NRs) are present in human ONH a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 78 publications
4
49
0
Order By: Relevance
“…Only recently has a specific role for astrocytes in this process received any attention. Astrocytes in the ONH have been implicated in elevated intraocular pressure and ganglion cell death in glaucoma (Cooper et al, 2015; Dai et al, 2012; Ju et al, 2015). Although the implications are not clear, here we show that there are similar structural changes in ONH astrocytes in response to retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently has a specific role for astrocytes in this process received any attention. Astrocytes in the ONH have been implicated in elevated intraocular pressure and ganglion cell death in glaucoma (Cooper et al, 2015; Dai et al, 2012; Ju et al, 2015). Although the implications are not clear, here we show that there are similar structural changes in ONH astrocytes in response to retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from our group and others indicates that compromised mitochondrial dynamics, metabolic stress and mitochondrial dysfunction by glaucomatous insults such as elevated intraocular pressure (IOP) and oxidative stress are critical to RGC loss in experimental glaucoma [8][9][10][11][12][13][14][15][16][17][18][19] . Despite the widely appreciated disease relevance of mitochondrial dysfunction and loss, the molecular mechanisms underlying the impairment of mitochondrial structure and function in glaucoma are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in RGC death in glaucoma are complicated. The elevated intraocular pressure (IOP) is considered to be the major risk factor (Osborne, 2008; Ju et al, 2015; Yang et al, 2016), and lowering the IOP is thus far the only relatively effective treatment clinically (Chen et al, 2013; Itakura et al, 2015). However, lowering the IOP is not sufficient to prevent or delay progressive vision loss, and the molecular mechanisms underlying accelerated RGC loss, even when the raised IOP is lowered to a normal level for many years, remain poorly understood (Gupta and Yücel, 2007; Osborne, 2010).…”
mentioning
confidence: 99%
“…The neuroprotective effects against elevated pressure exerted by lithium chloride and iNOS were involved in regulating the mitochondrial dynamic proteins DRP1 and OPA1, respectively (Dai et al, 2011). Recently, Ju et al (2015) found that increasing mitochondrial fission, volume density and length protected astrocytes in glaucomatous neurodegeneration. Moreover, many studies have indicated that mitochondrial abnormalities occur in primary open-angle glaucoma patients, including increasing mitochondrial DNA (mtDNA) pathogenic mutations and content as well as decreasing mitochondrial respiratory activity (Abu-Amero et al, 2011; Nucci et al, 2013; Sundaresan et al, 2015).…”
mentioning
confidence: 99%